Metastatic SQSTM1-NTRK1 fused non-small-cell lung cancer treated with larotrectinib and stereotactic radiosurgery resulting in durable complete response: a case report - Colton Betts; Ari Kassardjian; Arya Amini (Therapeutic Advances in Medical Oncology)
Lung cancer is one of the most common malignancies and causes the most cancer deaths in the United States. Targeted therapies have improved the survival of patients with advanced disease. Neurotrophic tropomyosin receptor kinase (NTRK) fusions are a rare oncogenic driver that has been targeted with the tumor-agnostic drug, larotrectinib. There are limited data on the treatment of non-small-cell lung cancer (NSCLC) with larotrectinib because of the rarity of this fusion in this population. We present the case of a patient who was diagnosed with SQSTM1-NTRK1 fused NSCLC with polymetastatic disease involving the brain and subsequently treated with a multidisciplinary approach via neurosurgical resection, radiotherapy, and larotrectinib. The combination of aggressive local treatments and systemic therapy is a relatively new treatment paradigm and represents a new area of research to optimize local control of metastatic lesions and potentially improve progression-free survival compared to the trials that show the efficacy of systemic monotherapies. The patient has experienced a sustained complete response to treatment almost 3 years later, and he has tolerated the drug without any significant adverse effects. The combination of systemic therapy with larotrectinib and aggressive local treatments could benefit patients with targetable fusions even with multiple metastatic lesions.